2014
DOI: 10.1007/s11552-014-9694-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cold Sensitivity in Patients with Hand Pathology

Abstract: Background The purpose of this study was to evaluate the prevalence of cold sensitivity in patients with hand-and wristrelated diagnoses. Methods We included English-speaking adults who were more than 1 month following hand injury or onset of symptoms. Patients were asked if exposure to cold air or water provoked cold-related symptoms and to rank symptom severity (scale 0-10). Statistical analyses evaluated the relationships between the cold sensitivity and independent variables (age, gender, history of trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Cold sensitivity was associated with less improvement following surgery 9 . These results correspond well to our results, and the frequencies are similar to those seen after hand trauma 10,11 . In a normal population, cold sensitivity, defined as > 50 in CISS or by > 4 on a 10-point VAS (visual analogue scale), has been reported in 5-14% 10,12 , the higher prevalence being found in the northern parts of Sweden, where the climate is generally colder than in the south of the country.…”
Section: Discussionsupporting
confidence: 92%
“…Cold sensitivity was associated with less improvement following surgery 9 . These results correspond well to our results, and the frequencies are similar to those seen after hand trauma 10,11 . In a normal population, cold sensitivity, defined as > 50 in CISS or by > 4 on a 10-point VAS (visual analogue scale), has been reported in 5-14% 10,12 , the higher prevalence being found in the northern parts of Sweden, where the climate is generally colder than in the south of the country.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported a prevalence of 38–83% in patients with post-traumatic cold sensitivity, although many studies have been limited by small and selected patient samples (Carlsson et al., 2010b; Craigen et al., 1999; Graham and Schofield, 2008; Novak et al., 2012; Ruijs et al., 2007). To measure the prevalence of cold sensitivity in patients with upper extremity disorders, Novak and McCabe (2015) assessed 197 patients that were referred with various disorders of the hand and found that 34% of the patients reported cold-induced symptoms. Although significantly more patients with traumatic injuries were affected, 27% of those without injuries had cold-induced symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Severe symptoms of cold sensitivity and pain have been reported following upper extremity trauma and negatively affect outcome and health-related quality of life (QoL). 3,[5][6][7][8]10,[14][15][16] The assessment of cold sensitivity has included objective measures such as skin temperature and rewarming patterns and self-report questionnaires. 2,10,11,[17][18][19]21 These evaluation methods have illustrated a wide range of responses that occur with cold provocation and cold sensitivity after upper extremity trauma.…”
Section: Introductionmentioning
confidence: 99%